Photoreceptor-dependent regulation of photoprotection. (June 2017) - Allorent, Guillaume; Petroutsos, Dimitris
Highlights: Photoreception and photoprotection are tightly linked in photosynthetic organisms. Chloroplast relocation is crucial for the regulation of absorbed light. Blue and UV-B photoreceptors are novel regulators of qE in Chlamydomonas . Bridging photobiology and photosynthesis will boost photoprotection studies. Abstract : In photosynthetic organisms, proteins in the light-harvesting complex (LHC) harvest light energy to fuel photosynthesis, whereas photoreceptor proteins are activated by the different wavelengths of the light spectrum to regulate cellular functions. Under conditions of excess light, blue-light photoreceptors activate chloroplast avoidance movements in sessile plants, and blue- and green-light photoreceptors cause motile algae to swim away from intense light. Simultaneously, LHCs switch from light-harvesting mode to energy-dissipation mode, which was thought to be independent of photoreceptor-signaling up until recently. Recent advances, however, indicate that energy dissipation in green algae is controlled by photoreceptors activated by blue and UV-B light, and new molecular links have been established between photoreception and photoprotection.